Legal interaction of public authorities and individuals in the works of N.G. Salischeva: scientific providence - Serguey A. Poryvaev; Diana M. Mustafina-Bredikhina (RUDN Journal of Law, 2022)
The purpose of this article is to trace the scientific path of the development of the views of N.G. Salischeva, a prominent administrative scientist of the Soviet and Russian periods, on the interaction of the interests of individuals and public authorities, and active participation of a citizen in such legal relations. The article examines the researcher’s works of different years and her evolving views on the issues of personality perception in administrative law and administrative process with the help of synthesis and analysis. The authors investigate the perception of Salischeva’s positions and ideas in the Russian legislation, in scientific doctrine, as well as on outlined by her issues of furthering legal regulation of public power and strengthening the role of person and citizen in the administrative process, in terms of changes in the Russian society. In conclusion, the authors note Salishcheva’s contribution to the development of codified normative legal acts on administrative offenses, both during the Soviet period and the formation of Russian legislation.